"Miejsce podmiotu jako miejsce obce". Paul Ricoeur i Bernhard Waldenfels o odpowiedzialności - Krynicka, Anna (Er(r)go. Teoria - Literatura - Kultura, 2006)
Anna Krynicka, “Subject’s Alien Location.” Paul Ricoeur and Bernhard Waldenfels on Responsibility Taking as a departure point the notion of responsibility analysed here in the context of contemporary philosophy, the article revolves around the complexity of the relation between narrative identity and locality.